2021
DOI: 10.1136/bmjopen-2020-043595
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of echocardiographic left atrial size for incident stoke and stroke cause mortality: a population-based study

Abstract: ObjectivesTo investigate the associations between echocardiographic left atrial (LA) size and incident stoke and stroke cause mortality among a rural population in China.DesignA prospective study.Setting and participantsBased on the Northeast China Rural Cardiovascular Health Study, we selected a total of 10 041 participants aged ≥35 years who agreed to have transthoracic echocardiography at baseline and were successfully followed up for incident stoke and stroke cause mortality.Primary outcome measureThe outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…When analyzed as a categorical variable, the pooled results of five studies with 88,702 individuals [ 11 , 19 22 ] showed that a higher LA diameter was related to an increased risk of ischemic stroke (HR 1.39; 95% CI 1.06–1.82; I 2 = 72%) (Fig. 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…When analyzed as a categorical variable, the pooled results of five studies with 88,702 individuals [ 11 , 19 22 ] showed that a higher LA diameter was related to an increased risk of ischemic stroke (HR 1.39; 95% CI 1.06–1.82; I 2 = 72%) (Fig. 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…LA size was also significantly smaller in survivors. Previous studies both in the general population (Li et al, 2021; Patel et al, 2015) and in ESRD participants (Patel et al, 2010; Tripepi et al, 2007) have shown LA size to be a significant predictor of adverse outcomes. As an easily, reliably, and reproducibly acquired measure using standard 2‐D echocardiography, routinely acquired LA size may provide further prognostic information in ESRD participants.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, there is convincing evidence demonstrating that echocardiographic left atrial dimensions are predictors of major adverse cardiovascular events in patients both with and without atrial fibrillation. [88][89][90][91] Importantly, two studies showed that left atrial reservoir strain assessed by speckle-tracking echocardiography is independently associated with prior stroke or a predictor of incident stroke, 38,66 with a higher predictive value than the CHA 2 DS 2 VASc score, 38 indicating its potential value in improving current stroke risk stratification schemes. However, speckle-tracking analysis is challenging, especially during atrial fibrillation because of irregular cardiac cycles.…”
Section: Discussionmentioning
confidence: 99%